TEACHER QUESTIONS IN ENGLISH CLASSROOM - Angelina. N. F. Limbong; Sri Minda Murni (Universitas Negeri Medan, 2018)
The objective of this study was to find out the levels of questions used by teacher in English classroom and revealing the underlying reasons why teacher ask questions to the students in the classroom. This study was conducted by using descriptive qualitative research design. The subjects of this study is one of English teacher who teach in eighth grade students in one of school SMP in Pakpak Bharat that is SMP N 1 Kerajaan in academic year 2016/2017. The data were collected by video recording and interviewing the English teacher. The data were analyzed by using Miles and Huberman data analysis technique. The findings of the study were shown there were four levels of questions used by the teacher in English classroom from six levels of questions based on Bloom Taxonomy in Anderson and Krathwohl, with the total of questions were 117 in two meetings. Teacher spent remembering level 56% (66 questions), understanding level 31% (36 questions), applying level were 4% (5 questions), analyzing level were 9% (10 questions), evaluating level 0% and creating level 0%. From those levels, the dominance is discovered to be at the level of remembering, known as Lower Cognitive Questions (LCQ). This study also found that the underlying reasons of teacher ask questions in the classroom is to stimulate students’ interest, to encourage students focus to think when students learn, to know students understanding, and to give participation when they learn. It can be concluded that the teacher’s questions are as the technique of teaching.